Capital structure effects on the prices of equity call options - Geske, Robert; Subrahmanyam, Avanidhar; Zhou, Yi (Journal of Financial Economics, 2016)
We examine whether values of equity options traded on individual firms are sensitive to the firm’s capital structure. We estimate the compound option (CO) model, which views equity as an option on the firm. Compared with the Black-Scholes model, the CO model with a term structure of volatility (TSV) reduces pricing errors by 20% on average. The compound option effect is particularly strong for highly levered firms and long-term options, in which the pricing improvement is up to 70% of the Black-Scholes error. Without a TSV, the CO model reduces pricing errors of in-the-money options by 12.74% on average and for out-of-the-money by 9.22%. We show that the CO model implies a market value of firm leverage and allows imputation of the firm’s implied volatility, both of which have potential applications in corporate finance.